PUBLIC AFFAIRS DIVISION END OF 19950700 (Tufts Archival Research Center, 2007)
Marginalia; Draft; Budget statement for TI Public Affairs Division for 1995 as of end of July. Focuses on OSHA, environmental tobacco smoke (ETS), advertising and smoking bans and economic impact, and grants to labor, tax, and agricultural organizations.